Skillful multiyear predictions of ocean acidification in the California Current System - Riley X. Brady (Nature Portfolio, 2020)
Threats to marine ecosystems are increasing due to ocean acidification, but trends are spatiotemporally difficult to monitor or predict. Here the authors use an Earth system model to accurately predict surface pH changes in the economically and ecologically important California Current System.